2011
DOI: 10.1089/hum.2011.031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Existing Immunity on Gene Transfer to Nonhuman Primate Liver with Adeno-Associated Virus 8 Vectors

Abstract: Vectors based on the primate-derived adeno-associated virus serotype 8 (AAV8) are being evaluated in preclinical and clinical models. Natural infections with related AAVs activate memory B cells that produce antibodies capable of modulating the efficacy and safety of the vector. We have evaluated the biology of AAV8 gene transfer in macaque liver, with a focus on assessing the impact of pre-existing humoral immunity. Twenty-one macaques with various levels of AAV neutralizing antibody (NAb) were injected intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
173
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 173 publications
(180 citation statements)
references
References 39 publications
7
173
0
Order By: Relevance
“…S1). The expression construct, flanked by AAV2 inverted terminal repeats, was packaged in an AAV serotype 8 capsid and purified on an iodixanol gradient as previously described (33).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1). The expression construct, flanked by AAV2 inverted terminal repeats, was packaged in an AAV serotype 8 capsid and purified on an iodixanol gradient as previously described (33).…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from tissues and vector genomes quantified by Taqman PCR as previously described (33). …”
Section: Methodsmentioning
confidence: 99%
“…AAV8 NAb titer greater than 10 was enough to significantly reduce transduction of the liver. 4 On AAV1-and AAV5-injected animals a NAb titer of 1/160 and 1/80 respectively was enough to significantly inhibit transduction.…”
Section: Figmentioning
confidence: 98%
“…We and others have demonstrated that low levels of preexisting NAb to AAV vectors in monkeys have a profound impact on gene transfer [1][2][3] and redistribution of the vector to other organs such as the spleen. 4 The natural presence of AAV NAbs was not considered to have an impact in nonprimate animal models because their natural AAVs were thought to be serologically different from primate AAVs. A study was conducted to demonstrate this hypothesis.…”
mentioning
confidence: 99%
“…Many species, including dogs, sheep, pigs, macaques, and humans, have serum-circulating neutralizing antibodies (NAbs) to AAV at various levels, [4][5][6][7][8][9][10][11] with a strong correlation between AAV NAbs and the AAV serotype recovered from tissues. For example, the most prevalent AAV serotype in humans, AAV2, is also associated with a higher prevalence of AAV2 NAbs in the population, 10,12,13 whereas, on the contrary, AAV8, a nonhuman AAV, has higher prevalence among rhesus and cynomolgus macaques.…”
Section: Introductionmentioning
confidence: 99%